Organization and Logistics Process of Products Called "Abarrotes" of a Supermarket - Cáceres, André Aguirre (2018)
The objective is to show the organization and the logistics process in the grocery area of a supermarket, as well as its inventory control in order to be able to understand the way in which a company carries out its logistics tasks